Implementasi Nilai-Nilai Tri Hita Karana dalam Atraksi Wisata di Pura Desa dan Puseh Desa Adat Batuan - Dewa Ketut Wisnawa (UHN IGB Sugriwa Denpasar, 2020)
Tourism plays an important role in supporting the economy while preserving cultural values. To preserve culture from the influence of tourism globalization, it is necessary to measure the implementation of the Tri Hita Karana concept. Desa and Puseh Temple of Batuan Pakraman Village, aside from being a sacred place, also become a cultural preservation and tourist attraction. To narrow the study and limit this research, the researcher formulated the problem as follows: (1) How is the Implementation of Tri Hita Karana Values in Tourist Visits at Desa and Puseh Temple, Batuan Pakraman Village, Sukawati District, Gianyar Regency? (2) What Obstacles Faced in Implementing the Tri Hita Karana Values in Desa and Puseh Temple of Batuan Pakraman Village Sukawati District Gianyar Regency? (3) What is the Impact of Tourist Visits on the Tri Hita Karana Values in Desa and Puseh , Batuan Pakraman Village, Sukawati District, Gianyar Regency? This study was qualitative research. The data collection method used three techniques, namely: observation, interview, and literature study. The findings of this study were the implementation of Tri Hita Karana values in tourist visits in Desa and Puseh Temple, Batuan Pakraman Village, Sukawati District, Gianyar Regency, covering Implementation in the Field of Palemahan, Pawongan and Parahayangan. The implementation done by preserve the sacred and cleaning activities.